Interdependent Mechanisms for Processing Gender and Emotion: The Special Status of Angry Male Faces - Harris, Daniel A.; Ciaramitaro, Vivian M. (Frontiers in Psychology, 2016)
While some models of how various attributes of a face are processed have posited that face features, invariant physical cues such as gender or ethnicity as well as variant social cues such as emotion, may be processed independently (e.g., Bruce and Young, 1986), other models suggest a more distributed representation and interdependent processing (e.g., Haxby et al., 2000). Here, we use a contingent adaptation paradigm to investigate if mechanisms for processing the gender and emotion of a face are interdependent and symmetric across the happy–angry emotional continuum and regardless of the gender of the face. We simultaneously adapted participants to angry female faces and happy male faces (Experiment 1) or to happy female faces and angry male faces (Experiment 2). In Experiment 1, we found evidence for contingent adaptation, with simultaneous aftereffects in opposite directions: male faces were biased toward angry while female faces were biased toward happy. Interestingly, in the complementary Experiment 2, we did not find evidence for contingent adaptation, with both male and female faces biased toward angry. Our results highlight that evidence for contingent adaptation and the underlying interdependent face processing mechanisms that would allow for contingent adaptation may only be evident for certain combinations of face features. Such limits may be especially important in the case of social cues given how maladaptive it may be to stop responding to threatening information, with male angry faces considered to be the most threatening. The underlying neuronal mechanisms that could account for such asymmetric effects in contingent adaptation remain to be elucidated.